Upaya Peningkatan Ekonomi Anggota Bank Sampah ‘Satu Hati’, melalui Pengelolaan dan Pemanfaatan Limbah Sampah di Kelurahan Sumber Mulyo Rejo, Binjai Timur - hanna meilani damanik; Martin Luter Purba; Hendrik E.S Samosir; Nancy Nopeline; Manatap Berliana Lumban Gaol (Jurnal Visi Pengabdian Kepada Masyarakat, 2023)
The aims of the service is to provide information and education to the people in the Sumber Mulyo, one of sub-district in Binjai especially the members of ‘Satu Hati’ Garbage Bank. regarding household waste management and provide practical training to develop new products with higher economic value by empowering garbage. This activity was carried out in the form of lectures and training on Maggot cultivation (Black Fly Soldier / BFS) and egg shell processing which was attended by members of the 'Satu Hati’ Waste Bank. Through this activity of organic eggshell waste it is hoped that members of the ‘Satu Hati’ Garbage Bank will gain new knowledge that can be practically implemented to deal with waste and can also receive economic benefits through the processing and Maggot cultivation.